Management of Movable Waqf Assets: A Study of Religious Institutions - Fadila Rahmadani; Emrizal Emrizal; Nil Firdaus; Dodon Alfiander (ZAWA: Management of Zakat and Waqf Journal, 2026)
This research is motivated by the importance of professional management of movable waqf assets, such as ambulances, in order to ensure that they continue to serve their intended purpose (ta’bid al-manfa’ah). Although the ambulances at the Istiqamah Mosque have provided extensive social services, there are still administrative challenges regarding their legal status and the sustainability of their operational costs. This study aims to analyse the implementation of management functions and compliance with waqf regulations. The study employs a qualitative method using a case study design. Data were collected through observation, documentation and in-depth interviews with mosque administrators (nazir) and representatives of the waqf donors. Data analysis followed the Miles and Huberman model. The results of the analysis show that, firstly, management has implemented the planning, organizing, actuating, and controlling framework in practice, but has not yet optimised it in terms of long-term maintenance budget planning. Secondly, from a positive law perspective, the management has not yet complied with the provisions of Article 10 of Law No. 41 of 2004 and Article 17 of Government Regulation No. 42 of 2006, as the assets have not been officially registered and do not yet have a Deed of Waqf. Thirdly, the main constraints are the reliance of operational costs on public donations and the Nazhir’s lack of understanding of the administrative procedures governing movable waqf assets. This study recommends the need for competency certification for Nazhirs and the acceleration of asset legalisation to ensure the legal security of the waqf.